Konsep Pelayanan Garuda Indonesia Experience dan Konstruksi Makna dalam Network Society - Sriherlambang, Budi (Bina Nusantara University, 2015)
As one of the largest airlines in Indonesia, Garuda Indonesia Airlines has launched a service concept of the Garuda Indonesia Experience. The paradigm shifting of the society has lead into high interconnection among people through the development of technology. Network society starts to emerge as the interconnection of the people starts to grow. How this shift will affect patterns of human behavior into an observed phenomenon that needs to be maximized positively. The shift that will be observed is a focus on process consumption on a product or service. As a company that has to maintain their sustainable growth, it is important for Garuda Indonesia to understands the relationship between this shift in society with their new service concept, the Garuda Indonesia Experience. This study reviewed the literature to find linkages and opportunities in the future so that an organization can continue to run in any changes to the consumer.